An extended evaluation of the weathering hypothesis for birthweight - Samuel Fishman (Demographic Research, 2020)
Background: Prior weathering research finds that US-born Black women experience more rapidly deteriorating birthweight outcomes at older ages than US-born White women. Objective: The present study extends this literature by evaluating maternal age-birthweight associations across a variety of racial/ethnic-nativity groups. Methods: Race/ethnicity-nativity stratified average marginal effects of maternal age on low and very low birthweight are estimated using data from 2014 through 2018 US cohort natality files. Results: Older maternal ages at birth are associated with higher probabilities of low and very low birthweight for most racial/ethnic-nativity groups. Consistent with the weathering hypothesis, birth at older maternal ages (e.g., 30‒34 or 40+) is more predictive of low and very low birthweight for US-born Black, American Indian/Alaskan Native, and US-born Mexican American women than for US-born Whites. In contrast, some foreign-born populations exhibit relatively weak relationships between maternal age and low birthweight, suggesting the role of healthy immigrant selection. Contribution: Some disadvantaged racial/ethnic-nativity groups ‒ US-born Black, American Indian/Alaskan Native, and US-born Mexican American women ‒ exhibit more rapid increases in the risk of low birthweight at older maternal ages than US-born White women. These patterns are consistent with the weathering hypothesis. Future research may benefit from using linked family data and sibling modeling approaches to estimate causal models of weathering.